2016
DOI: 10.1021/acsami.6b12508
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Self-Assembly of Atomically Precise Graphene Nanoribbons into Uniform Thin Films for Electronics Applications

Abstract: Because of their intriguing electronic and optical properties, atomically precise graphene nanoribbons (GNRs) are considered to be promising materials for electronics and photovoltaics. However, significant aggregation and low solubility of GNRs in conventional solvents result in their poor processability for materials characterization and device studies. In this paper, we demonstrate a new fabrication approach for large-scale uniform thin films of nonfunctionalized atomically precise chevron-type GNRs. The me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 25 publications
(52 citation statements)
references
References 41 publications
5
47
0
Order By: Relevance
“…Following the scooping transfer the cGNR-COFs adopt orientations in which the lateral spacing between cGNRs (2.5 nm) lies on an axis perpendicular to the surface and remains out of focus leaving only the πstacking and linker-linker distances to be observed by in-plane elastic scattering. Most notably, the HR-TEM demonstrates that the crystalline domain size (> 400 nm 2 ) is 1-2 orders of magnitude larger than previously reported solution processable GNR films formed via π-stacking alone 27 . cGNR-COFs not only self-assemble into larger crystallites but macromolecular reticulation through directional covalent bonds allows for the rational design of highly anisotropic materials.…”
mentioning
confidence: 55%
“…Following the scooping transfer the cGNR-COFs adopt orientations in which the lateral spacing between cGNRs (2.5 nm) lies on an axis perpendicular to the surface and remains out of focus leaving only the πstacking and linker-linker distances to be observed by in-plane elastic scattering. Most notably, the HR-TEM demonstrates that the crystalline domain size (> 400 nm 2 ) is 1-2 orders of magnitude larger than previously reported solution processable GNR films formed via π-stacking alone 27 . cGNR-COFs not only self-assemble into larger crystallites but macromolecular reticulation through directional covalent bonds allows for the rational design of highly anisotropic materials.…”
mentioning
confidence: 55%
“…GNRs can easily aggregate in the solid state and in solution due to the strong π-π interactions between their large conjugated sp 2 -carbon planes. Both physical approaches (i.e., sonication exfoliation [26] and chemical treatment with a strong acid [53]) have been tested for enhancing the liquid-phase GNR dispersion. However, these approaches generally have limited dispersion effects and visible agglomerates remain.…”
Section: Synthetic Strategies Toward Liquid-phase-processable Gnrsmentioning
confidence: 99%
“…Müllen and colleagues reported that alkyl chain-substituted HBCs formed a discotic liquidcrystalline phase associated with high charge-carrier mobility [59][60][61]. In comparison with smaller HBCs, the supramolecular behavior of GNRs in the liquid phase is less frequently investigated, mainly due to their poor liquid-phase dispersibility [53,62,63]. Although alkyl chain-functionalized GNRs can self-organize into monolayers at the solid-liquid interface ( Figure 1F), their poor dispersibility in organic solvents limits the diversity of GNR supramolecular nanostructures.…”
Section: Supramolecular Nanostructures Of Peo-functionalized Gnrsmentioning
confidence: 99%
“…38 These solvents, in which a certain amount of GNRs could be dispersed for hours, are promising for the solution processing of nanoribbons. Noteworthy, we recently demonstrated that another solvent that proved to be very effective for dispersing graphene and carbon nanotubes, chlorosulfonic acid, 23,30 can be also be used to form stable solutions of GNRs 14,46 at concentrations as high as 15 mg mL À1 , 46 but for some applications it is preferable to have GNRs dispersed in less corrosive solvents.…”
Section: Dispersions Of Gnrs and Their Optical Propertiesmentioning
confidence: 99%
“…These nanoribbons already have been a subject of several theoretical [39][40][41] and experimental studies. 2,5,[42][43][44][45][46][47][48] We investigated chevron GNRs in solution and found that their optical properties depend on their aggregation state. We also found that in addition to forming bulk aggregates of the p-p stacked nanoribbons, on surfaces GNRs can assemble to form long one-dimensional (1D) structures.…”
Section: Introductionmentioning
confidence: 99%